Highland Shepherd : James MacGregor, Father of the Scottish Enlightenment in Nova Scotia - Wilson, Alan, 1927- (Book collections on Project MUSE., 2015)
Alan Wilson brings MacGregor and his surroundings to life, detailing his numerous achievements and establishing his importance to the social, religious, and intellectual history of the Maritimes.